FAKTOR PENENTU STRUKTUR MODAL PADA PERUSAHAAN KELUARGA DAN NONKELUARGA DI INDONESIA - CLAUDIA PRANANDA; ULYSVASHTIEN UTAMA; RINANINGSIH; VANIA PRADIPTA GUNAWAN (Jurnal Bisnis dan Akuntansi, 2019)
This research aims to examine and analyze the determinants of capital structure in family business and nonfamily business. This research uses sample of 370 companies listed on BEI from 2012 to 2016 using the purposive sampling method. This research uses determinants of capital structure, such as, growth opportunities, debt cost, age, cash flow, size, non-debt tax shield, and investment. Debt to asset ratio is used as the proxy of capital structure. Results show growth opportunities and debt cost have negative relationship with capital structure, however size has positive relationship with capital structure in all firms in Indonesia. Furthermore, family ownership strengthens the negative relationship of debt cost, age, and cash flow on capital structure, however size weakens the positive relationship with capital structure.